2018
DOI: 10.1038/s41375-018-0123-z
|View full text |Cite
|
Sign up to set email alerts
|

Baricitinib-induced blockade of interferon gamma receptor and interleukin-6 receptor for the prevention and treatment of graft-versus-host disease

Abstract: The therapeutic benefits of allogeneic hematopoietic stem cell transplantation (allo-HSCT) are derived from the graft-versus-leukemia (GvL) effects of the procedure. There is a strong association between the GvL effects and graft-versus-host disease (GvHD), a major life-threatening complication of allo-HSCT. The limiting of GvHD while maintaining the GvL effect remains the goal of allo-HSCT. Therefore, identifying optimal therapeutic targets to selectively suppress GvHD while maintaining the GvL effects repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 41 publications
(57 reference statements)
2
79
0
Order By: Relevance
“…One can conclude that any JAKinib would have an equivalent effect on T cells in the treatment of TAK. However, baricitinib seems to be more efficient than ruxolitinib to increase Tregs proportion among human primary T cells, through preservation of JAK3/STAT5 signalling pathway 23. These results raise the question of whether a specific JAKinib should be preferentially indicated in the TAK treatment.…”
Section: Discussionmentioning
confidence: 98%
“…One can conclude that any JAKinib would have an equivalent effect on T cells in the treatment of TAK. However, baricitinib seems to be more efficient than ruxolitinib to increase Tregs proportion among human primary T cells, through preservation of JAK3/STAT5 signalling pathway 23. These results raise the question of whether a specific JAKinib should be preferentially indicated in the TAK treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Allogeneic hematopoietic stem cell transplantation (allo‐HSCT) is helpful in the management of hematological malignancies and derived from graft‐versus‐leukemia (GvL) outcomes, which are modulated by T cells existing in the donor graft. On the other hand, the same donor T cells can also modulate the graft‐versus‐host disease (GvHD), that it is the main cause of death among allo‐HSCT recipients (Choi et al, 2018). It is demonstrated that baricitinib inhibits IFN‐γR and IL‐6R signaling and prevents GvHD with 100% survival, expanded regulatory T cells and inhibited the expression of MHC II (Choi et al, 2018).…”
Section: Clinical Developmentsmentioning
confidence: 99%
“…On the other hand, the same donor T cells can also modulate the graft‐versus‐host disease (GvHD), that it is the main cause of death among allo‐HSCT recipients (Choi et al, 2018). It is demonstrated that baricitinib inhibits IFN‐γR and IL‐6R signaling and prevents GvHD with 100% survival, expanded regulatory T cells and inhibited the expression of MHC II (Choi et al, 2018). Also, baricitinib conserves the GvL effects possibly through downregulating tumor PD‐L1 expression (Choi et al, 2018).…”
Section: Clinical Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, also effects on Tregs (i.e., frequency) were investigated and a potential association between Tregs and the clinical response was explored. However, the amount of data presented in published studies (i.e., on local and systemic Treg frequency and functionality in mice and men, but also in vitro) was much more extensive than present in the dossier reports, although for one of the JAK inhibitors only one literature study was available (151)(152)(153)(154)(155)(156)(157)(158).…”
Section: Other Products Affecting Treg-relevant Targetsmentioning
confidence: 99%